Laboratory Investigation of the Behavior of Helical Piles under Monotonic Loading at Different Loading Speeds - Seyed Sajjad Hosseini; Mohsen Keramati; Reza Hoseinpour (مهندسی عمران شریف)
Today, one of the primary challenges faced by geotechnical engineers in dealing with problematic soils is to choose a suitable improvement method that, in addition to strengthening the soil, does not cause harmful damage to the environment. Helical piles are a new method that has become very popular in recent years due to the unique features of this type of pile, the most important of which is that it is environmentally friendly. Due to their unique shape and section (having one or more helices along the shaft of the pile), Helical piles have a higher load capacity than usual concrete piles. Among the advantages of using this type of pile, it can be a short installation time with minimal noise and vibration (no need to vibrate for installation), is Easy to implement due to limited access, lightweight, reduction of disturbance soil during installation, and poses less environmental risks and is compatible with nature. According to past studies, it has been found that the current knowledge of the performance of this type of pile and the methods of predicting and determining the bearing capacity currently need to be improved, and this shows the necessity of researching the behavior of these piles. This research, to predict the tensile behavior of Helical piles under different loading speeds and also to investigate the addition of a second helix to a single-helix Helical pile, using the 1g physical modeling device, in two cases of high (95%) and low (45%) relative densities, has been studied. The results obtained in this study show that the effect of relative soil compaction on improving the bearing capacity of the soil was more significant than the loading speed and the number of helices. According to the results of the monotonic tests, the final bearing capacity decreased by about 56% with increasing loading speed; on the other hand, by increasing the relative density and increasing the number of helices, the final load capacity increased, respectively by about 468% and 54%.